Independent and combined associations of depression and cognitive impairment with frailty in oldest-old adults - Xiaoguang Zhao; Xiaosha Duan; Shaoshuai Shen; Jin Wang (BMC Psychology, 2024)
Abstract Background Frailty is one of the most significant issues related to human aging. Although studies have confirmed the association of mental and cognitive disorders with frailty, the association might be influenced by age, since oldest-old adults are more likely to have adverse health outcomes. Thus, this study aimed to examine independent and combined associations of mental health and cognitive function with frailty in oldest-old adults using data from the Chinese Longitudinal Healthy Longevity Survey in 2018. Methods A sum of 6,891 and 3,171 older adults aged 80 and older were included in this study when analyzing the association of depression and cognitive impairment with frailty, respectively. Frailty was measured by the Study of Osteoporotic Fractures frailty index, depression was assessed by the Center for Epidemiologic Studies Depression Scale, and cognitive impairment was evaluated by the Chinese version of modified Mini-Mental State Examination. Independent sample t-test, Chi-square tests, and logistic regression analyses were used to examine the associations of depression and cognitive impairment with frailty. Results Older persons with depression or cognitive impairment had a higher chance of frailty. The adjusted odds ratio (OR) of frailty was 1.27 (95% CI: 1.01, 1.59, p = 0.044) in those with depression, and 1.85 (95% CI: 1.14, 3.01, p = 0.013) in those with cognitive impairment. Compared to adults who had neither depression nor cognitive impairment, those with either depression or cognitive impairment, and those with both depression and cognitive impairment had a significantly higher likelihood of frailty (adjusted OR: 1.61, 95% CI: 1.07, 2.41; and adjusted OR: 4.03, 95% CI: 2.05, 7.94). Conclusions The findings suggest that depression and cognitive impairment are associated with frailty. The concurrence of depression and cognitive impairment has an additive effect on frailty in oldest-old population.